Increasing physical activity a practical guide - Rippe, James M. (Lifestyle medicine series, 2021)
"The health benefits of regular physical activity are beyond dispute, yet less than 40% of physicians routinely counsel their patients on the importance of physical activity. Increasing Physical Activity: A Practical Guide equips healthcare practitioners to include physical activity counseling in the daily practice of medicine."--Provided by publisher.